Diverse bio-sensing and therapeutic applications of plasmon enhanced nanostructures. (July 2022) - Mitra, Shirsendu; Basak, Mitali
Graphical abstract: Abstract: Substantial advancements have been observed over the years in the research and development of Localized Surface Plasmon Resonance (LSPR). A variety of current and future applications involving anisotropic plasmonic nanoparticles include biosensors, photothermal therapies, photocatalysis, and various other fields. Amongst various other applications, plasmonic enhancements are deployed in Surface Enhanced Raman Spectroscopy (SERS) mediated bio-sensing, absorption spectroscopy based analyte quantification, and fluorescence spectroscopy-based biomolecular detection up to femtomolar level and even on the level of single molecules. LSPR based healthcare diagnostics and therapeutics have grown much faster than expected, with an increased number of published original research articles and reviews. Despite the extensive literature available, a comprehensive review with a focused emphasis on recent advances in the field of plasmonic particle anisotropy, plasmonic nanostructure, plasmonic coupling mediated enhanced LSPR intensity and their diverse applications in biosensing is needed. This article focuses on LSPR properties of anisotropic nanostructures like spherical gold nanoparticles (AuNP), gold nanorod (AuNR), gold nanostar (AuNs), gold nanorattles (AuNRT), gold nanoholes (AuNH), dimeric nanostructures and their role in plasmonic enhancements for targeted biosensing and therapeutic research. The contemporary state of the art biosensing development around SERS has also been discussed. A detailed literature analysis of recent development in micro-surgery, photothermal tumor killing, biosensor development for detection up to single molecule level, high-efficiency drug delivery are covered in this article. Furthermore, recent and advanced technologies including Spatially Offset Raman Spectroscopy (SORS), Surface Enhanced Resonance Raman Spectroscopy (SERRS), and Surface Enhanced Spatially Offset Raman Spectroscopy (SESORS) are presented citing their importance in biosensing. We complement this review article with relevant theoretical frameworks to understand finer nuances within the literature that is discussed.